Chapter Dai primi trattati portoghesi di astronomia alla «Nube di Magellano» di Haroldo de Campos - Graziani, Michela (Studi e saggi, 2021)
Starting with the first astronomical treatises of the 16th century, this work focuses on the metaliterary concept of travel and on the attraction that astronomy, specifically the Magellanic clouds, produce in the Portuguese treaties of the modern age and in the Portuguese and Brazilian literature of the 20th century.